Analysis of Local Economic Development (LED) in Gunung Sewu Geopark (Case Study on Geosite Gunungkidul, DIY Province) - Azizah, Puspa Dewi; Nasikh, Nasikh; Soesilowati, Etty (Journal of Finance and Business Digital, 2024)
Indonesia is rich in geological heritage, including the Gunung Sewu Geopark, a significant geotourism site. However, excessive tourism threatens its sustainability, highlighting the need for an effective geotourism development strategy. This study examines local economic development in Gunungkidul Regency, focusing on six dimensions: target groups, location factors, policy focus, sustainable development, governance, and management processes. Using a descriptive quantitative approach, the findings reveal that four dimensions are in excellent condition, while two are in good condition. Despite its commendable state, the geopark requires strategies prioritizing local economic development, as the local economy is key to sustainable geopark management. Addressing the leverage factors in each dimension can enhance the sustainability of Gunungkidul’s geotourism, ensuring long-term benefits for the community and the environment.